Pelatihan Multimedia Interaktif Bagi Guru Guru SMP Negeri 1 Karangawen Demak - Achmad Buchori; Noviana Dini Rahmawati; Dina Prasetyowati; Ika Menariati; Agus Setiawan (Journal of Dedicators Community, 2021)
One of the technological innovations so that learning becomes conducive, interactive, interesting and can help teachers make evaluations of students to use the Kahoot platform. Kahoots are in the form of game applications, quiz choices, or opinion surveys and public opinions of students or institutional members conducted online through a web browser. The problem with partners is that the teachers of SMP Negeri 1 Karangawen, Demak Regency still need refreshment in making interactive multimedia.  The methods  applied  in  this  service  program  are the presentation methods, demonstration methods, and practice methods. The presentation method was applied in the introduction of Kahoot software, ProProfs, Prezi of its usefulness, and its application in making interactive learning media, Demonstration Methods regarding program operationalization and Practice Methods where teachers directly practiced making instructional media in accordance with their respective subjects using Kahoot programs, ProProfs, Lectora, and Prezi